2023
DOI: 10.1128/mbio.03469-22
|View full text |Cite
|
Sign up to set email alerts
|

Peptidyl tRNA Hydrolase Is Required for Robust Prolyl-tRNA Turnover in Mycobacterium tuberculosis

Abstract: Peptidyl tRNA hydrolase (Pth) is an enzyme that cuts unfinished peptides off tRNA that has been prematurely released from a stalled ribosome. Pth is essential in nearly all bacteria, including the pathogen Mycobacterium tuberculosis (Mtb), but it has not been clear why.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The observation that MenT3 only targets tRNA Ser isoacceptors in vivo and that cytidine elongations are significantly shorter in vivo (1 to 5) than in vitro (up to 17) suggests more stringent conditions in vivo or/and that other factors would contribute to such a strong preference in vivo. Remarkably, as observed in E. coli (Avcilar-Kucukgoze et al , 2016) and in humans (Evans et al , 2017), tRNA Ser are significantly less aminoacylated than other tRNAs in M. tuberculosis , with less than 20% of tRNA Ser being charged when at steady state (Tomasi et al , 2023). Such a low charging of tRNA Ser was proposed to be due to a competition between aminoacylation of tRNA Ser for translation and the need for serine amino acids for pyruvate and acetate production and glycine synthesis in E. coli (Avcilar-Kucukgoze et al , 2016).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The observation that MenT3 only targets tRNA Ser isoacceptors in vivo and that cytidine elongations are significantly shorter in vivo (1 to 5) than in vitro (up to 17) suggests more stringent conditions in vivo or/and that other factors would contribute to such a strong preference in vivo. Remarkably, as observed in E. coli (Avcilar-Kucukgoze et al , 2016) and in humans (Evans et al , 2017), tRNA Ser are significantly less aminoacylated than other tRNAs in M. tuberculosis , with less than 20% of tRNA Ser being charged when at steady state (Tomasi et al , 2023). Such a low charging of tRNA Ser was proposed to be due to a competition between aminoacylation of tRNA Ser for translation and the need for serine amino acids for pyruvate and acetate production and glycine synthesis in E. coli (Avcilar-Kucukgoze et al , 2016).…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, the low availability of endogenous charged tRNA Ser in M. tuberculosis would exacerbate the deleterious effect of MenT3 and contribute to the evolution of a strong preference for tRNA Ser in vivo . The targeting of specific tRNAs is a characteristic of many toxin families (Songailiene et al , 2020; Yashiro et al , 2021; Tomasi et al , 2023; Cheverton et al , 2016; Wilcox et al , 2018; Zhang et al , 2020; Kurata et al , 2021; Li et al , 2021; Vang Nielsen et al , 2019). In M. tuberculosis , the acetyltransferase toxin TacT (Rv0919) was shown to specifically acetylate the primary amine group of charged tRNA Gly glycyl-tRNAs (Tomasi et al , 2023), and the PIN domain RNase toxin VapC-mt4 was shown to cleave a single site within the anticodon sequence of tRNA Cys (Barth et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence, or highly limiting amounts, of functional UUA-decoding tRNA, the presence of stimulatory signals for hypothetical frameshifting at the adpA UAA could influence the proportion of GATase 1 that is immediately degraded or released in a functional state following frameshifting mediated termination (or out-of-frame bypassing). An alternative possibility for liberating functional upstream-encoded product, GATase 1, is that when a UUA codon is in the ribosomal A-site and functional cognate tRNA is unavailable, peptidyl-tRNA drops off the ribosome and the ester linkage of the peptide to the tRNA is cleaved by a peptidyl-tRNA hydrolase (pth) [ 20 , 21 ]. One of the recoding signals for the 30% to 50% efficient translational bypassing of 50 nucleotides required for synthesis of a phage T4-encoded topoisomerase subunit is relevant to the extent of drop-off in that system [ 22 ].…”
Section: Introductionmentioning
confidence: 99%